Survei Tingkat Kecemasan Matematika Pada Siswa Sekolah Dasar - Fadila, Fauziah Nur (MISOOL: Jurnal Pendidikan Dasar, 2025)
Mathematics anxiety is a significant barrier to students' academic success, particularly among elementary school students. This study aimed to examine the level of mathematics anxiety among students at SDIT Salafiyah Syafi’iyah. Using a quantitative survey method, data were collected from 34 students through a validated and reliable questionnaire. The results showed that the average mathematics anxiety score was 31.68, which falls within the moderate category. Furthermore, 47.06% of students experienced moderate anxiety, 23.53% experienced high anxiety, and 29.41% experienced low anxiety. These findings indicate that nearly 70% of students face mathematics anxiety at moderate to high levels. The questionnaire used demonstrated strong psychometric properties, with all 12 items showing valid results and a high reliability coefficient (Cronbach’s Alpha = 0.966). This study highlights the urgent need for emotional support and anxiety-reducing strategies in early mathematics education to improve students’ confidence, motivation, and learning outcomes.